PKA‐binding domain of AKAP8 is essential for direct interaction with DPY30 protein. (22nd January 2018) - Bieluszewska, Anna; Weglewska, Martyna; Bieluszewski, Tomasz; Lesniewicz, Krzysztof; Poreba, Elzbieta
Abstract : The main function of the A kinase‐anchoring proteins (AKAPs) is to target the cyclic AMP‐dependent protein kinase A (PKA) to its cellular substrates through the interaction with its regulatory subunits. Besides anchoring of PKA, AKAP8 participates in regulating the histone H3 lysine 4 (H3K4) histone methyltransferase (HMT) complexes. It is also involved in DNA replication, apoptosis, transcriptional silencing of rRNA genes, alternative splicing, and chromatin condensation during mitosis. In this study, we focused on the interaction between AKAP8 and the core subunit of all known H3K4 HMT complexes—DPY30 protein. Here, we demonstrate that the PKA‐binding domain of AKAP8 and the C‐terminal domain of DPY30, also called Dpy‐30 motif, are crucial for the interaction between these proteins. We show that a single amino acid substitution in DPY30 L69D affects its dimerization and completely abolishes its interaction with AKAP8 and another DPY30‐binding partner brefeldin A‐inhibited guanine nucleotide‐exchange protein 1 (BIG1), which is also AKAP domain‐containing protein. We further demonstrate that AKAP8 interacts with DPY30 and the RII alpha regulatory subunit of PKA both in the interphase and in mitotic cells, and we show evidences that AKAP8L, a homologue of AKAP8, interacts with core subunits of the H3K4 HMT complexes, which suggests its role as a potential regulator of these complexes. The results presented here reinforce the analogy between AKAP8–RII alpha and AKAP8–DPY30 interactions, postulated before, and improve our understanding of the complexity of the cellular functions of the AKAP8 protein. Abstract : A kinase‐anchoring protein 8 (AKAP8) participates in regulating H3K4 histone methyltransferase (HMT) complexes. We demonstrate that the interaction between AKAP8 and the core subunit of histone H3 lysine 4 (H3K4) HMT complexes, DPY30 protein, shows structural analogy to the complex composed of AKAP8 and the cyclic AMP‐dependent protein kinase A regulatory subunit. We also show evidences that A‐kinase anchoring protein 8 like, a homologue of AKAP8, interacts with core subunits of H3K4 HMT complexes.